KASIH SAYANG ORANG TUA YANG CUKUP DAN DAMPAKNYA PADA HASIL BELAJAR PESERTA DIDIK DI SD ISLAMIC VILLAGE TANGERANG - Sulistiawati, Nining (el-Moona: Jurnal Ilmu Pendidikan Islam, 2023)
The fulfillment of parental affection can affect the learning outcomes of students. Influential things include external factors, namely the family environment, school, community and internal factors, namely from the student himself, including interests and talents. This study uses a qualitative approach using a literature research method. The findings of this study are as follows: The form of fulfilling parental affection at SD Islamic Village Tangerang which starts from the environment in the form of fulfilling the basic needs of students, namely fulfillment in terms of psychology and materials. The achievement of student learning outcomes is seen in 3 aspects, namely the cognitive domain which focuses on intellectual learning outcomes, a change in behavior that occurs in cognition as a benchmark is academic achievement of test scores above average, subject olympiad competitions. The affective realm, measured by communication skills, for example, EF speaking competitions, speech competitions. The psychomotor realm, which is the realm related to the skills and ability of students to act in body movements which are manifested in swimming, pencak silat and other sports competitions. The contribution of the fulfillment of parental affection to the improvement of student learning outcomes at SD Islamic Village Tangerang is a form of concern for their children, parents who care about their children will definitely continue to follow their children's development and ensure that their children are in good condition. Meet all children's needs both materially and psychologically, support all children's needs and ensure that their children are well monitored.